Educating tourists for global citizenship: a microfinance tourism providers' perspective. Issue 2 (3rd April 2017) - Phi, Giang Thi; Whitford, Michelle; Dredge, Dianne; Reid, Sacha
ABSTRACT: Ethical tourism initiatives have increasingly been framed as tools to educate tourists about global citizenship (GC), yet it is unclear how these initiatives are conceptualised, planned and implemented by tourism providers. This paper focuses on a form of ethical tourism known as microfinance tourism (MFT). It critically explores MFT providers' perspectives on what constitutes the goals of educating tourists about GC and how MFT can be designed and implemented to achieve these goals. The study adopted a qualitative approach utilising in-depth interviews with 12 key informants from 6 MFT organisations in Tanzania, Mexico, Jordan and Vietnam. The results reveal that MFT providers rely on an experiential learning process to educate tourists. However, as part of this learning process, MFT initiatives are located on a continuum, constituting those initiatives designed to increase tourists' compassion and philanthropic actions (i.e. 'thin' GC) through to those initiatives seeking to build solidarity and global discussions between tourists in order to challenge the structures that perpetuate global injustice (i.e. 'thick' GC). These results highlight the diversity of tourism providers' perspectives pertaining to GC, the effect diversity has on the design of tourism initiatives and the resultant outcomes of GC education utilising ethical tourism.